2016
DOI: 10.1021/jacs.6b02871
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation-Driven “Reverse Mars–van Krevelen”-Type Radical Mechanism for Low-Temperature C–O Bond Activation

Abstract: C-O bond activation on monofunctional catalysts (metals, carbides, and oxides) is challenging due to activity constraints imposed by energy scaling relationships. Yet, contrary to predictions, recently discovered multifunctional metal/metal oxide catalysts (e.g., Rh/ReOx, Rh/MoOx, Ir/VOx) demonstrate unusually high C-O scission activity at moderate temperatures. Herein, we use extensive density functional theory calculations, first-principles microkinetic modeling, and electronic structure analysis to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 94 publications
7
72
0
Order By: Relevance
“…However, the formation of furan is thermodynamically favored on Pd surfaces, in agreement with experimental observations . Computational studies detailing the mechanism of furfural hydrodeoxygenation to furfuryl alcohol, furan, and MF have also been reported on Pt and Ru surfaces. Cai et al .…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the formation of furan is thermodynamically favored on Pd surfaces, in agreement with experimental observations . Computational studies detailing the mechanism of furfural hydrodeoxygenation to furfuryl alcohol, furan, and MF have also been reported on Pt and Ru surfaces. Cai et al .…”
Section: Introductionsupporting
confidence: 82%
“…Recent studies by Mironenko et al. on Ru(0 0 1) surfaces report electronic energy barriers of 75 and 123 kJ mol −1 for the former and latter pathways . Also, (C 4 H 3 O)CHOH is 38 kJ mol −1 less stable than (C 4 H 3 O)CH 2 O, making (C 4 H 3 O)CHOH formation both thermodynamically and kinetically less favorable than (C 4 H 3 O)CH 2 O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…pointed out that C−O bonds can be further weakened if biomass‐oxygenate is adsorbed on the oxygen vacancy sites of MoO 3 catalysts . Moreover, Mironenko and Vlachos noted that RuO 2 oxygen vacancies promote C−O band scission . Previously, we found that oxygen vacancies on RuO 2 /C catalysts favor the cleavage of O−H in water .…”
Section: Introductionmentioning
confidence: 70%
“…O atoms are attracted by the coordinately unsaturated Mo. The oxidized sites are reduced sequentially by H 2 to close the redox cycle and the reduced oxygenate desorbs from the surface . It is most likely that more than one cycle leads to the formation of propylene.…”
Section: Resultsmentioning
confidence: 99%